If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(3x + 2) = 2x + -32 Reorder the terms: 7x + -1(2 + 3x) = 2x + -32 7x + (2 * -1 + 3x * -1) = 2x + -32 7x + (-2 + -3x) = 2x + -32 Reorder the terms: -2 + 7x + -3x = 2x + -32 Combine like terms: 7x + -3x = 4x -2 + 4x = 2x + -32 Reorder the terms: -2 + 4x = -32 + 2x Solving -2 + 4x = -32 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 4x + -2x = -32 + 2x + -2x Combine like terms: 4x + -2x = 2x -2 + 2x = -32 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 2x = -32 + 0 -2 + 2x = -32 Add '2' to each side of the equation. -2 + 2 + 2x = -32 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -32 + 2 2x = -32 + 2 Combine like terms: -32 + 2 = -30 2x = -30 Divide each side by '2'. x = -15 Simplifying x = -15
| 4x+3y=356 | | 4(6b-8)=36+7b | | 1/6(x+12)-1/8(x-8) | | 3x-13=47 | | 50X6/10-6+36 | | 5x^2-40x+84=0 | | (6+25-7)/6= | | 10x+5=6x+99 | | 4(3w-7)=6(2w+5) | | 5/2y=14 | | 3x+18/y=21 | | (-16t^2+136t+72)=0 | | c=3.14*2 | | 2/7x^2-6=21 | | 0.9(6x+12)=1.2-(x+2) | | (3)2m+3=192 | | 2x*7y=26 | | 1.4/7.9= | | 3x^2-56x+640=0 | | 2x*7y= | | 6x-13=2x-3 | | -7+X^2-3x=0 | | 5(x^2+3)=59 | | x^2+30x+75=7 | | W-8.7=2.32 | | 60k+60=50k+100 | | 12x^6/4x^2 | | 100(1-1/k^2)=89 | | 52-6x=16+12x | | x^2-15=-9 | | 100(1-1/k^2)=36 | | -9*-11/3 |